Optimasi Formulasi Masker Gel Peel-off dengan Ekstrak Kulit Putih Buah Semangka (Citrullus lanatus) menggunakan Variasi Konsentrasi Karbopol 940: Optimization of the Peel-off Gel Mask Formulation with Watermelon (Citrullus lanatus) White Peel Extract Using Variations in Carbopol 940 Concentrations - Widyani Budiarti; Hermini Tetrasari; Neni Rahmani; Dita Andhyni (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Antioxidant compounds were known to reduce the reactivity of free radicals, thereby helping to prevent damage to cells and bodily molecules. These compounds were commonly found in various plants and fruits and were considered relatively safer than synthetic antioxidants. In this study, the author utilized white rind extract of watermelon (Citrullus lanatus) as a natural antioxidant source in the formulation of a peel-off gel face mask intended for dry skin, using different concentrations of carbopol 940 as a gelling agent. An experimental method was employed, involving formulation development and product evaluation. Based on the assessment of three peel-off mask formulations containing 3.5% watermelon white rind extract, the optimal concentration of carbopol 940 was determined to be 0.5%. This conclusion was drawn from evaluations of homogeneity, organoleptic properties, spreadability, pH, viscosity, drying time, and product stability. The peel-off gel face mask formulated with 0.5% carbopol 940 and watermelon rind extract appears safe based on pH range and physical tests; however, further safety assessments. Keywords: Carbopol 940; Extract; Watermelon white rind; Face mask.